Reaction dynamics of separation-enhanced steam reforming of methanol for hydrogen production - Ye Lwin; Saiful Azhar, Saad; Khairul Nizar, Ismail; Mohamed Zulkali, Mohamed Daud (Universiti Putra Malaysia (UPM) & Institution of Chemical Engineers, Malaysia, 2008)
Organized by Universiti Putra Malaysia (UPM) & Institution of Chemical Engineers, Malaysia, 12th - 14th December 2007 at Universiti Putra Malaysia (UPM) Serdang, Selangor.